2021
DOI: 10.3390/f12101359
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Experiment of Cutting Mechanical Parameters for Caragana korshinskii (C.k.) Branches

Abstract: In order to investigate the cutting mechanical characteristics of Caragana Korshinskii (C.K.) branches and explore the optimal combination of cutting parameters to support the subsequent equipment development, this paper explores the relationship between branch diameter D, average cutting speed v, wedge angle β, slip cutting angle α, cutting height h, cutting gap t, moisture content M and peak cutting force by using a homemade swing-cut branch cutting test bench with peak cutting force of branches as the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Machines for splitting wood along the fibres (0°-90°) typically have a conical auger for splitting wood (Ober 1978;York 1983;Wentzell 1987;Bolton 2006;Erber and Stampfer 2020). Tests for breaking down wood transversely to the fibres (90°-90°) are mainly conducted on the heads of harvesters used for chipless cutting (Bergström and Di Fulvio 2014;Harvánek et al 2020;Gao et al 2021) or for limbing heads (Gerasimov et al 2012;Mederski et al 2018;Melicherčík et al 2021). Figure 13 presents a simulation of the process of splitting wood in direction B (0°-90°), while Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Machines for splitting wood along the fibres (0°-90°) typically have a conical auger for splitting wood (Ober 1978;York 1983;Wentzell 1987;Bolton 2006;Erber and Stampfer 2020). Tests for breaking down wood transversely to the fibres (90°-90°) are mainly conducted on the heads of harvesters used for chipless cutting (Bergström and Di Fulvio 2014;Harvánek et al 2020;Gao et al 2021) or for limbing heads (Gerasimov et al 2012;Mederski et al 2018;Melicherčík et al 2021). Figure 13 presents a simulation of the process of splitting wood in direction B (0°-90°), while Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the cutting performance of C.K. branches, Gao et al (2021) investigated the effect of cutting parameters on peak cutting force during supported and unsupported cutting using a selfdesigned pendulum cutting test stand. Since the pendulum cutting test bench uses the inertial force of the pendulum to cut the branches, its cutting speed is high, while the operating speed of the tool cannot be achieved in the actual operation process.…”
Section: Introductionmentioning
confidence: 99%
“…When using forest wood resources, cross-cutting to a preliminary dimension is often used, such as cutting a tree for logs and production of various wood products. Research on reducing energy consumption in wood processing machines is carried out by introducing innovations in cutting mechanisms [3][4][5], drives [6][7][8], or control system. The authors of [9] reported that lower values of cutting power were measured in transverse cutting of balks of coniferous (Spruce) than in deciduous wood (Beech).…”
Section: Introductionmentioning
confidence: 99%